Computing Kernels Implemented With A Wormhole RTR CCM - Bittner, Ray; Athanas, Peter (5th IEEE Symposium on FPGA-Based Custom Computing Machines (FCCM '97), 1997)
The wormhole run-time reconfiguration (RTR) computing paradigm is a method for creating high performance computational pipelines. The scalability, distributed control and data flow features of the paradigm allow it to fit neatly into the configurable computing machine (CCM) domain. To date, the field has been dominated by large bit-oriented devices whose flexibility can lead to lowered silicon utilization efficiencies. In an effort to raise this efficiency, the Colt CCM has been created based on the wormhole RTR paradigm. This paper outlines methods of implementation and performance for several common operations using these concepts. They serve as indicators of the diversity of algorithms that can be instantiated through the high-speed run-time reconfiguration that these devices make possible. Particular attention is paid to floating point multiplication. Also discussed is the topic of data dependent computation which would seem to be counter intuitive to the wormhole RTR paradigm. The paper concludes with a summary of performance of the three computations.